Determinants of Parents’ Delay for Diagnosis of Childhood Acute Lymphoblastic Leukemia at a Tertiary Care Hospital of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: It is very important to early diagnosis of cancer because it gives an opportunity for early treatment and prognosis. Unfortunately, late presentation and delayed diagnosis of childhood cancer remains a problem in developing countries including Bangladesh.Objectives: The purpose of the present study was to evaluate the factors behind parents’ delay in the diagnosis of acute lymphoblastic leukemia among children in a tertiary care hospital in Bangladesh.Methodology: This was a descriptive cross sectional study carried out in the Department of Pediatrics at Mymensingh Medical College Hospital, Mymensingh, Bangladesh from April 2013 to September 2013. Information was obtained from hospital records of children diagnosed as acute leukemia Information included socio-demographic variables, urbanization, parent education and other causes to delayed diagnosis of leukemia.Results: Seventy children (44 males, 26 females) were included where the most common age group was 5 to 10 years which was 37(52.9%). Among 70 acute leukemia patients 66 (94.3%) lived in rural area and 4(5.7%) lived in urban area. Most of the patients 59(89.3%) belongs to the low socioeconomic status and 11(15.7%) were from middle class family. Among the parents, 27(38.6%) fathers and 33(47.1%) mothers were illiterate. Delayed reaching tertiary care hospital after suspicion were lack of personal 2 (2.85%), economic constrain 6 (8.57%), lack of information about availability of proper treatment 1 (1.42%), other causes 30 (42.85%) and none 31(44.28%). Median lag time was 60 days.Conclusion: In conclusion factors contributing to delayed diagnosis are rural areas, parents’ education, economic constrain and urbanization.Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):26-31